ChemInform Abstract: Ruthenium Hydride/Broensted Acid‐Catalyzed Tandem Isomerization/N‐Acyliminium Cyclization Sequence for the Synthesis of Tetrahydro‐β‐carbolines. Issue 22 (3rd June 2014) - Hansen, Casper L.; Clausen, Janie W.; Ohm, Ragnhild G.; Ascic, Erhad; Le Quement, Sebastian T.; Tanner, David; Nielsen, Thomas E.
Abstract This new approach represents an attractive alternative to the classical Pictet—Spengler reaction.